2010
DOI: 10.1083/jcb.200912134
|View full text |Cite
|
Sign up to set email alerts
|

Clasp-mediated microtubule bundling regulates persistent motility and contact repulsion in Drosophila macrophages in vivo

Abstract: A microtubule arm regulates cell–cell repulsion, pointing hemocytes in opposite directions when they contact each other in Drosophila embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(162 citation statements)
references
References 41 publications
2
160
0
Order By: Relevance
“…For example, hemocytes are a potential alternative to S2 cells. Their harvest from embryos or larvae is effortless (Sampson & Williams, 2012), and their study in culture can be complemented by work in vivo, including live imaging of cytoskeletal dynamics in developmental or wound healing contexts (Beaven et al, 2015;Evans, Zanet, Wood, & Stramer, 2010;Stramer et al, 2010). Surprisingly, Shot has not yet been investigated in these cells.…”
Section: 2 Using Primary Cultures Combines Detailed Readouts With Pomentioning
confidence: 99%
“…For example, hemocytes are a potential alternative to S2 cells. Their harvest from embryos or larvae is effortless (Sampson & Williams, 2012), and their study in culture can be complemented by work in vivo, including live imaging of cytoskeletal dynamics in developmental or wound healing contexts (Beaven et al, 2015;Evans, Zanet, Wood, & Stramer, 2010;Stramer et al, 2010). Surprisingly, Shot has not yet been investigated in these cells.…”
Section: 2 Using Primary Cultures Combines Detailed Readouts With Pomentioning
confidence: 99%
“…5 a; Abercrombie and Heaysman, 1953). Its fundamental relevance in guiding migratory processes during embryonic development has been demonstrated in vivo for dispersion of macrophages (Stramer et al, 2010) and neurons (Villar-Cerviño et al, 2013) and for collective migration of neural crest cells . When two neural crest cells interact, they assemble a transient cell-cell junction, which contains the classical cadherin complex (Scarpa et al, 2015), but they eventually repolarize their protrusions in opposite directions and move away from one another (Fig.…”
Section: Contact Inhibition Of Locomotion: Polarizing the Collectivementioning
confidence: 99%
“…The nuclei were labelled with GFP-Moesin, which appeared red, whilst the microtubules were labelled with a green microtubule probe (Clip-GFP) [4]. RGB images of dimensions (n h , n w , n d ) = (512, 672, 3) and 541 time frames were acquired.…”
Section: Macrophages Embryosmentioning
confidence: 99%
“…It has been shown that interactions among the cells' structures appear to anticipate the direction of migration [4]. Precise analyses of cell shapes as they evolve through time, as well as the correct identification of interacting cells that overlap could provide information for specific cells in biological studies; where sharp corners suggest an active migrating cell and rounded corners inactivity [4]. Thus, accurate cell segmentation could provide information for specific cells for biological studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation